Intestinal parasites and genotypes of Giardia intestinalis in school children from Berisso, Argentina - Molina, Nora; Pezzani, Betina; Ciarmela, Maria; Orden, Alicia; Rosa, Diana; Apezteguía, Maria; Basualdo, Juan; Minvielle, Marta (The Journal of Infection in Developing Countries, 2011)
Introduction: Intestinal parasitic infections have been reported in different regions of Argentina. Giardia intestinalis is recognized as "the national parasite". The aim of this work was to determine the prevalence of both intestinal parasites and G. intestinalis genotypes, as well as to analyze the clinical and epidemiological characteristics in schoolchildren from a suburban community. Methodology: Serial coproparasitological analysis and perianal swab method were performed in 244 schoolchildren. Demographic, sociocultural and environmental variables were registered. The presence of signs/symptoms and risk behaviours were also recorded. Stools with G. intestinalis were selected for genotyping. Results: Out of 244 schoolchildren, 179/244 (73.4%) were infected with intestinal parasites. The presence of intestinal parasitosis was associated only with house flooding. Multivariate analysis identified that use of a latrine is significantly correlated with G. intestinalis and age six to 11 years with E. vermicularis. Signs and symptoms were recorded in 62% of infected children and in 57.9% of those not infected. Genomic amplification was revealed that 65.7% (46/70) of Giardia positive samples corresponded to genotype B, 31.4% (22/70) to genotype AII, and two samples (2.8%) had mixed infection (AII + B). Conclusions: This study shows a high percentage of infected children living in a suburban community in poor sanitary conditions, and not visiting the doctor in spite of evident signs and symptoms associated a digestive pathology. This situation supports the need for continuing the development of community programs allowing the improvement of quality of life and control of parasitosis in deprived populations.